Hereditary and Acquired Polyneuropathy Conditions of the Peripheral Nerves: Clinical Considerations and MR Neurography Imaging - Trivedi, Jaya R.; Phillips, Lauren; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2015)
Polyneuropathies can be classified as either primarily demyelinating or axonal, and further as hereditary or acquired. It is important to recognize acquired neuropathies because some are amenable to treatment. Clinical findings and electrophysiology are used in the routine diagnosis of these conditions. Magnetic resonance neurography (MRN) is a helpful supplementary diagnostic tool. This article discusses the typical clinical findings, electrophysiology findings, and MRN appearances of common hereditary or acquired neuropathies such as chronic inflammatory demyelinating neuropathy, multifocal motor neuropathy, diabetic neuropathy, chemotherapy-induced neuropathy, and postsurgical neuropathy.
Keywords: acquired neuropathy; hereditary neuropathy; demyelinating; axonal; MRN